Factors Affecting Consumer Purchase Intention on TikTok Shop towards Beauty industry among Asia Pacific University Students - Yiin, Tan Huey; Singh, Ninderpal Singh a/l Balwant; Dada, Morakinyo (Electronic Journal of Business and Management, 2024)
TikTok Shop, focusing on students at Asia Pacific University (APU). Using a quantitative research design, data were collected from 160 TikTok users who had previously purchased products from TikTok Shop. The analysis highlights the influence of perceived convenience, trustworthiness, and interaction on purchase intentions. Results reveal that all three factors significantly and positively impact consumer decisions, underscoring the importance of seamless shopping experiences, credible marketing approaches, and interactive engagement strategies. These findings provide valuable insights into consumer behaviour in social commerce and offer actionable recommendations for businesses aiming to optimise their marketing strategies on TikTok Shop.